DISAIN DAN INSTRUMEN PENILAIAN BEST PRACTICES PELAYANAN PUBLIK PEMERINTAH DAERAH DI ERA OTONOMI DAERAH - Deddy Mulyadi (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2019)
Decentralization is expected to bring about better public services for local citizens. Some regions have proved that they are able to provide better services to their citizens through decentralization. Several of them have even been able to produce innovations in the form of prime public services in certain fields. These widely known prime public services lead to the emergence of public service ‘best practices’ in some regions. The question is how to judge that the service delivery in a region can be categorized into a best practice. This article tries to convey some theoretical and practical design and instrument for evaluating whether or not the local services can be acknowledged as ‘best practices’. Thus in the future, there will be an objective guideline to evaluate ‘best practice’ services by using certain standardized term of reference.